2006
DOI: 10.1111/j.1538-7836.2006.01684.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA expression analyses from small‐scale, single‐donor platelet samples

Abstract: Summary.  Background: Comparisons of platelet RNAs could provide crucial information on platelet function, thrombopoiesis and the etiology of megakaryocyte (MK) or platelet disorders.Objectives: We developed a method for stringent purification of platelets from small blood samples from single donors. Purity of the platelet preparations was verified by an RT‐PCR assay. We tested three methods to identify the differences in RNA between platelet sources.Methods: Differential hybridization to cDNA macro‐arrays and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Our estimate of 7771 commonly expressed platelet genes was consistent with other reports of genome-wide microarray 27,31 and RNA-seq 16,18 analyses of smaller numbers of samples. The size of our dataset permits accurate estimates of platelet RNA levels in healthy subjects.…”
Section: Relevance To Platelet Biologysupporting
confidence: 90%
“…Our estimate of 7771 commonly expressed platelet genes was consistent with other reports of genome-wide microarray 27,31 and RNA-seq 16,18 analyses of smaller numbers of samples. The size of our dataset permits accurate estimates of platelet RNA levels in healthy subjects.…”
Section: Relevance To Platelet Biologysupporting
confidence: 90%
“…Thus, these previous studies assumed that changes in platelet function were at the posttranscriptional level. Platelets do contain reservoirs of mRNA, and a number of studies have reported the transcriptome of human platelets using mRNA profiling (11)(12)(13)(14). It has also been established that platelets regulate translation of their transcriptome in response to external stimuli (15)(16)(17).…”
mentioning
confidence: 99%
“…Only a few studies have considered differential platelet RNA expression in clinical hemorrhagic or thrombotic phenotypes, including complex phenotypes such as sickle cell disease or cardiovascular disease. [4][5][6][7] Platelet RNA profiling of ET has particular appeal considering that the transcripts are derived from the tissue of primary clinical and pathophysiologic interest. The success of these genomic approaches is critically dependent on the precision of the patient phenotyping, generally large numbers of subjects, and appropriate bioinformatic and statistical analyses.…”
Section: Platelet Rna Chips Dip Into Thrombocytosis -----------------mentioning
confidence: 99%
“…4,5 Whereas PN-1 is a potent and specific inhibitor of thrombin, PN-2 operates by an entirely different mechanism, characteristic of the kunins, to serve as a potent (K i ϳ 500pM) and highly specific inhibitor of the unique, homodimeric coagulation proteinase, factor XIa (FXIa). Both PN-2 and PN-1 are present in plasma at concentrations far too low to inhibit their cognate proteinases, but are secreted from platelet ␣-granules to achieve high concentrations (ϳ 30nM in the case of PN-2) in the surrounding plasma.…”
mentioning
confidence: 99%